Matériel sciences à vivre : cycle 2 - Lagraula, Dominique; Brach, Nicolas; Legoll, Dominique; Schneider, Léa (Accès éditions, 2016)
Le coffret accompagne les différents séances de l'ouvrage Sciences à vivre cycle 2